Sol-gel derived thin films of LiTaO3 on SiO2/Si substrates for optical waveguide applications - Cheng, Shi-De (2020)
Thin films of lithium tantalate have been derived on SiO2/Si substrate by sol-gel method. The sol is prepared by mixing LiOC2H5 and Ta(OC2H5)5. The film is deposited by spin- coating and annealing at 600°C. The film is characterized by means of X-ray diffraction, atomic force microscopy, and the m-line technique. The experimental results show that the film has crystallized into the pure trigonal phase and it is microsopically continuous and uniform. The crystalline size ranges from about 33nm to 96nm. The refractive index of the film is measured to be 1.84 at the wavelength of 633nm and the film is found to support several guiding modes at this wavelength. © 2001 Taylor & Francis.